PRE-NATAL DIAGNOSIS ULTRASONOGRAPHIC OF CONGENITAL MALFORMATIONS - Huamán C., Moisés (2015)
Thirty cases with pre-natal ultrasound diagnosis of congenital anomalies were reviewed. Seventy per cent of mothers were 25 to 34 year-old and 36.7% carried their first pregnancy. Most fetal anomalies were related to the neural axis (70.3%), mainly anencephalies (59%). Hydramnios was present in 56.6% of cases, various anomalies in 20%, and less frequent digestive and skeletal anomalies. Hydramnios occurred in 50.5% of neural axis anomalies. One half of the babies were male and sex was ambiguous in 2 cases. Birth weigth was less than 2500 gram. in 56.7% of cases.